Assessment at school – Teachers' diary-supported implementation of a training program. (November 2018) - Klug, Julia; Schultes, Marie-Therese; Spiel, Christiane
Abstract: Forty-seven secondary school teachers participated in a four-week training program on assessment strategies. A subgroup of 15 teachers documented their implementation of the training content and rated their reflective practice in standardized diaries. Teachers most often applied techniques of trying to avoid judgment biases, followed by systematic observation. The higher teachers' self-reported use of reflection and the greater the frequency of open reflection in the diaries, the better teachers' assessment competence was afterwards. In conclusion, some strategies seem to be easier to implement than others, and diaries have the potential to be not only evaluation tools, but also "intervention boosters". Highlights: Teachers most often apply techniques of trying to avoid judgment biases. The higher the self-reported use of reflection, the better teachers' assessment competence. The higher the frequency of open reflection, the better teachers' assessment competence. Diaries have the potential to be evaluation tools and "intervention boosters".